Acute myopericarditis presenting as effusive-constrictive pericarditis a case report - Adhikary, Dipal Krishna; Hasan, Md Nazmul; Siddique, Md Abu; Banerjee, Sajal Krishna; Iqbal, ATM; Hasan, Md Nazmul; Amin, Md Rasul (Bangladesh Medical Journal, 2016)
Myopericarditis is primarily a pericardial inflammatory syndrome occurring when clinical diagnostic criteria for pericarditis are satisfied and concurrent mild myocardial involvement is documented by elevation of biomarkers of myocardial damage (i.e. increased troponins). Limited clinical data on the causes of myopericarditis suggest that viral infections are among the most common causes in developed countries. Cardiotropic viruses can cause pericardial and myocardial in!ammation via direct cytolytic or cytotoxic effects and/or subsequent immune-mediated mechanisms. Many cases of myopericarditis are subclinical. In other patients, cardiac symptoms and signs are over shadowed by systemic manifestations of infection or inflammation. The increased sensitivity of troponin assay and contemporary widespread use of troponins has greatly increased the reported number of cases. Management is similar to that reported for pericarditis, generally with a empiric anti-inflammatory drugs mainly aimed to control symptoms. Rest and avoidance of physical activity beyond normal sedentary activities has been recommended for 6 months is recommended as for myocarditis. At present, there is no evidence that troponin elevation confers worse prognosis (i.e. a greater risk of recurrence, death or transplantation) in patients with preserved left ventricular function. Usually complete remission is seen in 3 to 6 months. We report here a case of a 18 year young man with acute myopericarditis who presented with transient effusive-constrictive pericarditis. Bangladesh Med J. 2015 Sep; 44 (3): 165-167